THERMAL CHARACTERISTICS OF CEMENT AND SOIL PONDS AND THEIR IMPLICATIONS FOR WATER QUALITY AND THE SURVIVAL OF GOURAMI FISH - Fadlilatul Husna; Yayat Ruhiat; Rudi Haryadi (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the differences in water quality between concrete and earthen ponds and their effects on the survival of gurami fish using a physical heat transfer approach. The study was conducted over 30 days using 100 gurami fish. Water quality parameters were measured and analyzed using SPSS and MATLAB. The results showed that the concrete pond outperformed the earthen pond in AWQI (65.8) and water chemistry parameters; however, the survival rate of fish in the earthen pond was higher (96.7%) than in the concrete pond (90.0%). This difference is explained by Fourier’s Law of Heat Conduction, where the lower thermal conductivity of soil (0.9 W/mK) results in better temperature stability (SD = 0.63) compared to concrete (1.7 W/mK; SD = 0.89). The study concludes that the thermal stability of earthen ponds provides a more adaptive environment for gurami fish.